1984
DOI: 10.1063/1.333004
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silicon produced by ion implantation: Effects of ion mass and thermal annealing

Abstract: Characterization of the two optical states of amorphous Si produced by ion implantation is extended to include electron paramagnetic resonance, fundamental absorption edge, and density measurements in addition to infrared reflection. It is found that the properties of the two a-Si states are not dependent upon the mass of the incident ion (12C, 29Si, 31P, 120Sn) or upon the anneal temperature for 400 °≤TA≤600 °C. The dangling-bond density drops about a factor of 2 when the a-Si makes a transition between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…One sample was pre-annealed at 523°C for about 9 minutes and then placed on the heater block for SPEG. This pre-annealing treatment almost completely relaxes the a-Si, according to the spectroscopy results of Waddell et al 50 and the calorimetry results of Donovan et al 44 (note time axis in Fig. 15).…”
Section: Search For An Effect On Speg Of Amorphous Relaxationmentioning
confidence: 49%
See 3 more Smart Citations
“…One sample was pre-annealed at 523°C for about 9 minutes and then placed on the heater block for SPEG. This pre-annealing treatment almost completely relaxes the a-Si, according to the spectroscopy results of Waddell et al 50 and the calorimetry results of Donovan et al 44 (note time axis in Fig. 15).…”
Section: Search For An Effect On Speg Of Amorphous Relaxationmentioning
confidence: 49%
“…On the basis of spectroscopic studies 48 , the two point defects that have been proposed are dangling bonds 48 (threefold-coordinated atoms) and floating bonds 49 (fivefold-coordinated atoms); both are analogous to the two predominant point defects in crystals (vacancies and interstitials). Waddell et al 50 have shown that for self-implanted a-Si, the concentration of spectroscopic defects decreases during structural relaxation by about a factor of 2 from 2x10 19 cm -3 after annealing at 500 o C.…”
Section: Search For An Effect On Speg Of Amorphous Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…Amorphous silicon (a-Si), a material with potential for application for SOT and large grained polysilicon TFT technologies, is also thought to be an ideal candidate for study of amorphous solids characterized as continuous random networks. Much work has been done in studying relaxation behavior in amorphous silicon, and many properties of a-Si were shown to be dependent on its degree of relaxation [1][2][3]. Recently, relaxation has been interpreted to occur by annihilation of point defects [3].…”
mentioning
confidence: 99%